Perlindungan Hukum terhadap Penyalahgunaan Identitas Digital Lembaga Pemerintah dalam Praktik Government Digital Impersonation di Indonesia - Desak Komang Putri Adnyani; Ni Putu Rai Yuliartini; Dewa Gede Sudika Mangku; I Putu Dwika Ariestu; I Gede Partama (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2026)
The rapid growth of digital government has increased the use of digital identities by public institutions to deliver information and public services. However, this development has also created new cyber threats, particularly government digital impersonation, where unauthorized parties misuse the digital identity of government institutions to commit fraud, disseminate misleading information, or obtain personal data unlawfully. This study aims to examine the legal framework governing the protection of government digital identities in Indonesia and to analyze the forms of legal protection and countermeasures against such practices. The research employs a normative legal method using statutory and conceptual approaches, supported by primary, secondary, and tertiary legal materials. The findings indicate that although Indonesia has established several legal instruments related to electronic information, personal data protection, and digital governance, the existing regulations have not specifically addressed government digital impersonation. Therefore, strengthening legal regulations, enhancing electronic system security, improving inter-agency coordination, and promoting digital literacy are essential to ensure more effective protection of government digital identities against evolving cyber threats.